Psychological Well-Being of Athletes: A Case Study on the National Arts and Sports Week (PESONA) I - Alfarizi, Abdul Khakim; Azmi, Faisal Mayshara; Sugiarti , Lucia Rini; Suhariadi, Fendy (Journal Corner of Education, Linguistics, and Literature, 2024)
The objective to be achieved in this study is to describe psychological well-being through the six factor model of psychological well-being in Athletes at the National Arts and Sports Week (Pesona) I. This type of research is qualitative research and uses a case study method. Data sources in this study include primary sources, namely the results of observations and interviews of three athletes at the National Arts and Sports Week (Pesona) I and secondary sources in the form of field documentation, social media, and articles. Data collection was carried out using observation, interviews, and documentation. Data analysis techniques were carried out using data reduction, data presentation, and drawing conclusions. Checking the validity of the data using data triangulation includes source triangulation, technique triangulation, and time triangulation. The results of the study showed that the description of the psychological well-being of 3 (three) outstanding students at the National Arts and Sports Week (Pesona) I who participated in this study showed that the subjects were in a state of psychological well-being.